Analyzing the Effectiveness of NAPTIP’s Enforcement Mechanisms in Combating Human Trafficking in Nigeria - Ibrahim S. Bello; Funke A. Okonjo (Law and Economy, 2025)
This study evaluates the effectiveness of the National Agency for the Prohibition of Trafficking in Persons (NAPTIP) in combating human trafficking in Nigeria. Through case studies and comparative analysis, the paper examines the agency’s enforcement mechanisms, including rescues, prosecutions, and victim reintegration efforts. Key challenges, such as resource constraints, judicial delays, and gaps in victim support, are identified and contextualized within Nigeria’s socio-political environment. A comparative assessment with similar agencies in Ghana and South Africa highlights best practices, such as leveraging technology and community reintegration programs, to enhance anti-trafficking efforts. The findings underscore the need for improved funding, operational efficiency, and international collaboration to sustain and scale NAPTIP’s impact on human trafficking networks.